2017
DOI: 10.14310/horm.2002.1721
|View full text |Cite
|
Sign up to set email alerts
|

Association between TPO Asn698Thr and Thr725Pro gene polymorphisms and serum anti-TPO levels in Iranian patients with subclinical hypothyroidism

Abstract: ObJeCTIVe: Subclinical hypothyroidism (SCH) is defined as high levels of TSH in the presence of normal levels of serum FT4. Since thyroid peroxidase (TPO) plays a key role in thyroid hormone synthesis, variations in the TPO gene can change the enzyme structure and result in the production of anti-TPO antibodies. The aim of this study was to examine the relationship between the Asn698Thr (A2095C) and Thr725Pro (A2173C) polymorphisms of the TPO gene and anti-TPO levels in patients with SCH. DESIGN: In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Although there have been previous reports of wrongly identified PCR primers and gene knockdown reagents in single articles or small cohorts ( 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 21 ), the present study is the first to systematically fact-check the identities of nucleotide sequences in more than 3,400 research articles. Our supported application of S&B ( 12 , 27 ) ( https://www.protocols.io/view/seek-amp-blastn-standard-operating-procedure-bjhpkj5n ) to screen three targeted corpora and two journals identified 712 articles published across 78 journals that described more than 1,500 wrongly identified sequences.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although there have been previous reports of wrongly identified PCR primers and gene knockdown reagents in single articles or small cohorts ( 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 21 ), the present study is the first to systematically fact-check the identities of nucleotide sequences in more than 3,400 research articles. Our supported application of S&B ( 12 , 27 ) ( https://www.protocols.io/view/seek-amp-blastn-standard-operating-procedure-bjhpkj5n ) to screen three targeted corpora and two journals identified 712 articles published across 78 journals that described more than 1,500 wrongly identified sequences.…”
Section: Discussionmentioning
confidence: 85%
“…Experiments that either attempt to replicate published results associated with incorrect reagents and/or unknowingly reuse incorrect reagents are likely to generate unexpected results that may then remain unpublished. As possible evidence of this, we could only identify one study that reported incorrect sequences based on the results of follow-up experiments ( 20 ) that our analyses also identified. Given that more than 17,000 citations have been accumulated by the problematic articles that we have identified, it seems inevitable that unreliable gene research articles are already wasting time and resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPOAb levels (and genotypes A2095C and A2173C) were significantly higher and more frequent in the subjects with SCH. The risk of developing SCH in the individuals with C alleles was higher than in the individuals without these alleles in the A2095C and A2173C regions, respectively [ 195 ].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Finally, due to cross-contamination and/or uncertainty over donor origins, many human cell lines are known to be wrongly identified (2125). These wrongly identified reagents can produce a range of downstream consequences, including failed attempts to reproduce published results (3, 5, 7, 11, 16), and potentially incorrect interpretations of preclinical data leading to misdirected translational research (10, 12, 25).…”
Section: Introductionmentioning
confidence: 99%